Making Devolution Work for Service Delivery in Kenya - Muwonge, Abdu; Williamson, Timothy Stephen; Owuor, Christine; Kinuthia, Muratha (Washington, DC: World Bank, 2022)
The Making Devolution Work for Service Delivery (MDWSD) study provides the first major assessment of Kenya’s devolution reform. The study provides key messages with respect to what is working, what is not working, and what could work better to enhance service delivery based on the currently available data. It provides an independent assessment of service delivery performance in five sectors, namely health, education, agriculture, urban, and water services and includes an in-depth review of the main pillars of devolved service delivery, namely public financial management, intergovernmental finance, human resource management, politics and accountability.